ENACT study: What has helped health and social care workers maintain their mental well‐being during the COVID‐19 pandemic?. (6th September 2022) - Cogan, Nicola; Kennedy, Chloe; Beck, Zoe; McInnes, Lisa; MacIntyre, Gillian; Morton, Liza; Tanner, Gary; Kolacz, Jacek
Abstract: A growing body of research has highlighted the adverse impact of COVID‐19 stressors on health and social care workers' (HSCWs) mental health. Complementing this work, we report on the psychosocial factors that have had both a positive and negative impact on the mental well‐being of HSCWs during the third lockdown period in Scotland. Using a cross‐sectional design, participants ( n  = 1364) completed an online survey providing quantitative data and free open‐text responses. A multi‐method approach to analysis was used. The majority of HSCWs were found to have low well‐being scores, high levels of COVID‐19 stress, worry, burnout and risk perception scores and almost half of HSCWs met the clinical cut‐off for acute stress (indicative of PTSD). HSCWs with higher scores on adaptive coping strategies and team resilience reported higher scores on mental well‐being. HSCWs were significantly more likely to seek informal support for dealing with personal or emotional problems compared to formal supports. Barriers to formal help‐seeking were identified including stigma and fear of the consequences of disclosure. HSCWs mostly valued peer support, workplace supports, visible leadership and teamwork in maintaining their mental well‐being. Our findings illuminate the complexity of the effects of the COVID‐19 pandemic on HSCWs' well‐being and will inform future intervention development seeking to increase positive adaptation and improve staff well‐being. Addressing barriers to mental health help‐seeking among HSCWs is essential. The implications emphasise the importance of lessons learned across health and social care contexts, planning and preparedness for future pandemics.